Peripherin immunoreactivity labels small diameter vestibular ‘bouton’ afferents in rodents - Lysakowski, Anna (1999)
Recent morphophysiological studies have described three different subpopulations of vestibular afferents. The purpose of this study was to determine whether peripherin, a 56-kDa type III intermediate filament protein present in small sensory neurons in dorsal root ganglion and spiral ganglion cells, would also label thin vestibular afferents. Peripherin immunohistochemistry was done on vestibular sensory organs (cristae ampullares, utriculi and sacculi) of chinchillas, rats, and mice. In these sensory organs, immunoreactivity was confined to the extrastriolar region of the utriculus and the peripheral region of the crista. The labelled terminals were all boutons, except for an occasional calyx. In vestibular ganglia, immunoreactivity was restricted to small vestibular ganglion cells with thin axons. The immunoreactive central axons of vestibular ganglion cells form narrow bundles as they pass through the caudal spinal trigeminal tract. As they exit this tract, several bundles coalesce to form a single, narrow bundle passing caudally through the ventral part of the lateral vestibular nucleus. Finally, we conclude that all labelled axons and terminals were vestibular afferents rather than efferents, as no immunoreactivity in the vestibular efferent nucleus of the brainstem was observed.